Combined DEM and SPH simulation of overflow ball mill discharge and trommel flow. (July 2017) - Sinnott, M.D.; Cleary, P.W.; Morrison, R.D.
Graphical abstract: Highlights: A coupled slurry-media model of mill discharge and trommel flow is developed. Fluid slurry in the mill lowers charge shoulder and toe due to drag forces. Trunnion spiral effectively returns balls back to the grinding chamber. Trommel baffles improve screening characteristics. DEM + SPH can help improve mill discharge performance and trommel classification. Abstract: Discharge of finer rock, pebbles, ball scats and slurry from mills and its flow through trommels and into other processing operations all affect the performance of overflow ball mills. Modelling of the coarser rock components and the grinding media is best done using the Discrete Element Method (DEM) while modelling of the slurry component is best done using a compatible particle method such as SPH (Smoothed Particle Hydrodynamics). This combination of methods allows both these critical components and their interactions to be included in flow models for the mill and discharge arrangements. Information from such models can be used to both understand the flows in these typically closed and data poor environments and to help optimise designs for improved performance and superior wear life. In this paper, a typical discharge/trommel arrangement for an overflow ball mill is analysed using this modelling approach with opportunities for use in process improvement discussed. In the mill grinding chamber the addition of slurry was found to lower the charge shoulder and toe positions due to drag forces on the media, as well as produce a large slurry pool above the toe. Slurry surging out of the grinding chamber carries mill product as well as a small amount of balls through the trunnion and into the trommel for classification. The trunnion spiral was found to be very effective at collecting and returning balls back into the mill grinding chamber. The rate of balls flowing into the trommel was found to be size-dependent favouring the discharge of smaller worn scats for removal as waste. Trommels with and without baffles were compared to establish linkages between transport and classification performance and trommel geometry. The inclusion of baffles inside the trommel was found to spread the slurry sideways and axially and provide improved screening characteristics.